(untitled) (Fiep Bulletin - online, 2011)
Professional educators have made efforts to analyze and collaborate on improving the quality of Childhood Education in the Brazilian reality. This research project, funded by the Nucleus Program for Teaching of UNESP, also assumes on this goal of progress in quality of Childhood Education and it is resultant of a partnership between the FCT / UNESP of Presidente Prudente and the Secretary of Education of the City of Alvares Machado, SP. It is supported by the Historic Cultural Theory and the Sociology of Childhood, because these two theoretical perspectives conceive the childhood with features and own identities and the children as interpretative and creative subjects, which the right to education it is directly related to participation, communication and the search for sense. Children to advance their development need educational proposals that address their interests and needs, focus on playful activities, fantasy and social interaction. However, it turns out in reality is that educational practices do not consider these assumptions and the child ends up suffering the consequences of this discrepancy between theory and practice. Because of this complex task of transformation of reality, the methodology that guides the research is action research. So far, diagnoses have been made about conceptions of education, childhood, child who guides the practices of teachers; beyond the recognition of the physical and material structure. It is ongoing the process of training of the participants in bi-weekly seminars; aimed at seeking a consensus level of conceptual and procedural enabling partnership and commitment to research. This perspective, we seek to involve teachers, in all dimensions: in defining the problems and needs, questions, study activities and methodology of the project. Once a week the participants, both from the university and partner institutions, carry out joint operations with the children, trying to achieve the objectives of the investigation.